The evolutionary background and functional consequences of the rs2071307 polymorphism in human tropoelastin. Issue 2 (22nd December 2020) - Reichheld, Sean E.; Muiznieks, Lisa D.; Huynh, Quang; Wang, Nick; Ing, Christopher; Miao, Ming; Sitarz, Eva E.; Pomès, Régis; Sharpe, Simon; Keeley, Fred W.
Abstract: Elastin is a major polymeric protein of the extracellular matrix, providing critical properties of extensibility and elastic recoil. The rs2071307 genomic polymorphism, resulting in the substitution of a serine for a glycine residue in a VPG motif in tropoelastin, has an unusually high minor allele frequency in humans. A consequence of such allelic heterozygosity would be the presence of a heterogeneous elastin polymer in up to 50% of the population, a situation which appears to be unique to Homo sapiens . VPG motifs are extremely common in hydrophobic domains of tropoelastins and are the sites of transient β‐turns that are essential for maintaining the conformational flexibility required for its function as an entropic elastomer. Earlier data demonstrated that single amino acid substitutions in tropoelastin can have functional consequences for polymeric elastin, particularly when present in mixed polymers. Here, using NMR and molecular dynamics approaches, we show the rs2071307 polymorphism reduces local propensity for β‐turn formation, with a consequent increase in polypeptide hydration and an expansion of the conformational ensemble manifested as an increased hydrodynamic radius, radius of gyration and asphericity. Furthermore, this substitution affects functional properties of polymeric elastin, particularly in heterogeneous polymers mimicking allelic heterozygosity. We discuss whether such effects, together with the unusually high minor allele frequency of the polymorphism, could imply some some evolutionary advantage for the heterozygous state. Abstract :